Understanding the digital world what you need to know about computers, the Internet, privacy, and security - Kernighan, Brian W. (Princeton University Press, 2017)
Computers are everywhere. Some of them are highly visible, in laptops, tablets, cell phones, and smart watches. But most are invisible, like those in appliances, cars, medical equipment, transportation systems, power grids, and weapons. We never see the myriad computers that quietly collect, share, and sometimes leak vast amounts of personal data about us. Through computers, governments and companies increasingly monitor what we do. Social networks and advertisers know far more about us than we should be comfortable with, using information we freely give them. Criminals have all-too-easy access to our data. Do we truly understand the power of computers in our world? Based on the author's Princeton course Computers in Our World, this book is intended as a compact but detailed and thorough explanation of how computers and communications systems work, for non-technical readers. It explains how today's computing and communications world operates, from hardware through software to the Internet and the web, also addressing the social, political and legal issues that new technology creates.